Basal metabolic characteristics of diabetics at sea level and a high altitude - Garmendia-Lorena, Fausto (2023)
Objective: A descriptive, analytical, cross-sectional study with a control group was carried out, in which the basal intermediarymetabolism of patients with type 2 Diabetes Mellitus (DM2) was compared, both at sea level (NM) and at altitude (ALT). Methodology: It has been studied at 33 DM2 of sea level (Lima, 150 m above sea level) and 28 DM2 of height (Cusco, 3395 masl), of both genders, from 40 to 70 years of age. Anthropometric measurements were taken and glucose (G), triglycerides (Tg), insulin (I), non-steroidal fatty acids (NAFA), total cholesterol (TC), HDL-C, triglycerides (Tg), LDL-C, LDL-C were determined under basal conditions., HDL-C; VLDL, LDL, and NoHDL cholesterol, glycosylated hemoglobin (HbA1c), and the HOMA coefficient were calculated. Statistical calculations using the SPSS v. 23. Results: High-altitude DM2 had significantly higher values of weight, height, HDL, Tg and AGNE. Discussion and Conclusions: Patients with DM2 exposed to a height of 3395 meters above sea level showed few metabolic differences compared to those DM2 patients at sea level.